2017
DOI: 10.5376/mpb.2017.08.0006
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization of Weedy Rice Populations from Different Regions of Asia

Abstract: Weedy rice produces a low number of grains per plant and is considered undesirable in cultivated rice fields. It spreads rapidly because of its high phenotypic plasticity and seed shattering. We used the RID14 marker to identify the genotypes governing red and white pericarp color in weedy rice. We then evaluated 18 characters of 199 weedy rice accessions (5 rice-growing regions in Asia) and 24 of cultivated rice as control, and analyzed them using coefficients of variation, principal component analysis, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Most morphological traits of weedy rice in this study showed an intermediate form between wild and cultivated rice (Figure 5), which is in line with other reports (Rathore, Singh, Kumar, & Chauhan, 2016; Sudianto et al, 2016; Zainuddin, Azmi, & Othman, 2010; Zhang et al, 2017). This also suggests that wild Oryza and elite cultivars genetically contribute to the complexity of Malaysian weedy rice (Song et al, 2014; Sudianto et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Most morphological traits of weedy rice in this study showed an intermediate form between wild and cultivated rice (Figure 5), which is in line with other reports (Rathore, Singh, Kumar, & Chauhan, 2016; Sudianto et al, 2016; Zainuddin, Azmi, & Othman, 2010; Zhang et al, 2017). This also suggests that wild Oryza and elite cultivars genetically contribute to the complexity of Malaysian weedy rice (Song et al, 2014; Sudianto et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Genomic sequencing and genetic diversity analyses have shown that the weedy rice populations from northeastern China are strongly associated with japonica rice cultivars and those from eastern China with indica rice cultivars, suggesting the independent feralization events occurred with distinct cultivated progenitors in different regions (Cao et al, 2006 ; Qiu et al, 2017 ). In addition to genetic divergence, morphological variations in hull color, awn length and color, grain length/width ratio, etc., have also been reported within and among populations (Zhang et al, 2017 ). Nevertheless, a notable feature that is shared by the weedy rice from eastern and northeastern China is that their seeds do not have primary dormancy.…”
Section: Introductionmentioning
confidence: 79%
“…Ciri morfologi dari weedy rice sangat berfariasi dari berbagai negara, di Malaysia mayoritas aksesi weedy rice berwarna coklat dan berbulu (Sudianto et al, 2016), warna pericarp aksesi weedy rice di Asia (Asia tenggara, Korea, China) bervariasi yaitu ada yang berwarna putih, coklat cerah, coklat spot, coklat, dan merah. Dari total aksesi 36, terdapat 11 berpericarp putih, 2 coklat dan 23 merah (Zhang et al, 2017).…”
Section: Morfologi Weedy Rice Yang Mendukung Eksistensinyaunclassified